2023
DOI: 10.31943/wej.v7i1.201
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian High School Students’ Demotivating Factors in Learning English

Abstract: Demotivation is a condition that occurs when a person begins to lose motivation or enthusiasm to do something and achieve specific goals. This demotivating condition can occur in various aspects of life, one of which is related to study. This study is aimed to investigate the demotivation factors of EFL High School students in learning English. Two students from a public high school in Indonesia were interviewed. The data were collected using two session interviews. The first session interview was about the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Students learn their skills and weaknesses as writers by reading what their teachers have written about them. Moreover, similar results also happened in Putra (2022) and Rasool et al (2023), who found that students experience demotivation and a sense of despair when confronted with intricate feedback conveyed through loops, underlining, and a lack of corrections and constructive input by the teacher. The preferred approach among students invariably centres on instructional techniques that involve clear explanations.…”
Section: 2%supporting
confidence: 68%
“…Students learn their skills and weaknesses as writers by reading what their teachers have written about them. Moreover, similar results also happened in Putra (2022) and Rasool et al (2023), who found that students experience demotivation and a sense of despair when confronted with intricate feedback conveyed through loops, underlining, and a lack of corrections and constructive input by the teacher. The preferred approach among students invariably centres on instructional techniques that involve clear explanations.…”
Section: 2%supporting
confidence: 68%
“…surroundings and find employment in the present and the future (Putra, 2020). To respond as the circumstance requires, it is important to ensure a solid command of the English language and effective communication skills.…”
mentioning
confidence: 99%
“…Several studies were conducted about the importance of English proficiency. The ability to communicate thoughts, sentiments and many other aspects more easily can be attributed to our proficiency in English (Putra, 2020). However, limited studies were conducted about maritime students' grammar, vocabulary, and speaking abilities.…”
mentioning
confidence: 99%